Healing with the chakra energy system acupressure, bodywork, and reflexology for total health - Cross, John R. Dr (North Atlantic Books, 2006)
"A physiotherapist and acupuncturist describes the complex energy centers of the chakras in detail as a therapeutic discipline and shows how they can be used with acupressure, bodywork, reflexology, cranio-sacral therapy, massage therapy, and healing"--Provided by publisher.